2019
DOI: 10.1371/journal.pgen.1008414
|View full text |Cite
|
Sign up to set email alerts
|

A candidate gene analysis and GWAS for genes associated with maternal nondisjunction of chromosome 21

Abstract: Human nondisjunction errors in oocytes are the leading cause of pregnancy loss, and for pregnancies that continue to term, the leading cause of intellectual disabilities and birth defects. For the first time, we have conducted a candidate gene and genome-wide association study to identify genes associated with maternal nondisjunction of chromosome 21 as a first step to understand predisposing factors. A total of 2,186 study participants were genotyped on the HumanOmniExpressExome-8v1-2 array. These participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 102 publications
2
32
0
Order By: Relevance
“…Previous studies have established a strong association between maternal age and incidence of meiotic error in preimplantation embryos (Hassold and Hunt 2001). Studies have also revealed significant, albeit modest, associations between aneuploidy rates and various fertility diagnoses (McCoy et al 2015b;Kort et al 2018), as well as patient genotypes (McCoy et al 2015a;Chernus et al 2019). One persistent concern with all studies of preimplantation embryos is the possibility that IVF culture conditions impact chromosome stability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established a strong association between maternal age and incidence of meiotic error in preimplantation embryos (Hassold and Hunt 2001). Studies have also revealed significant, albeit modest, associations between aneuploidy rates and various fertility diagnoses (McCoy et al 2015b;Kort et al 2018), as well as patient genotypes (McCoy et al 2015a;Chernus et al 2019). One persistent concern with all studies of preimplantation embryos is the possibility that IVF culture conditions impact chromosome stability.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the fact that Rec8 (cohesin) plays multiple roles during meiosis and that alterations in Rec8 result in abnormal gametes ( 23 , 49 ). Moreover, cohesin variation is linked to axis length and recombination rate differences that are linked to fertility in humans ( 24 , 50 , 51 ). Spore viability was more severely impaired at similar reductions of axis length by altering Rec8 than Pds5 (fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, genetic length is probably not the only explanation for chromosome-specific variation in the occurrence of E0s. For example, D group chromosomes (i.e., 13-15) had 1.3-fold the number of E0s as E group chromosomes (i.e., [16][17][18], although the genetic lengths of the two chromosome groups are virtually identical. 20,27 Possibly, the presence of extremely small p arms on acrocentric D and G group chromosomes increases the likelihood of E0 events.…”
Section: Discussionmentioning
confidence: 99%
“…We undertook the current large populationbased analysis to address important questions about the genesis of E0 chromosomes in the fetal ovary. Specifically, we asked whether there are among-individual differences in the incidence of recombination failure (e.g., due to allelic variation in recombination genes such as MSH4, SYCP3, or RNF212 15,16 ); whether the proportion of E0 chromosomes is influenced by gestational age (in accordance with the ''production line'' hypothesis of human nondisjunction, a model suggesting that the last fetal oocytes to enter meiosis have fewer crossovers and consequently are more likely to non-disjoin 17 ); or whether the incidence of E0s is influenced by maternal age (e.g., due to subtle changes in the fetal environment). We identified a surprisingly high level of recombination failure, with nearly 10% of all oocytes containing at least one exchangeless chromosome pair.…”
Section: Introductionmentioning
confidence: 99%